The role of TEMRA cell-mediated immune senescence in the development and treatment of HIV disease - Guo, Lihui; Liu, Xudong; Su, Xin (Frontiers in Immunology, 2023)
Human Immunodeficiency Virus (HIV) has plagued human society for a long time since its discovery, causing a large number of patients to suffer and costing hundreds of millions of medical services every year. Scientists have found that HIV and antiretroviral therapy accelerate immune aging by inducing mitochondrial dysfunction, and that terminal effector memory T cells (TEMRA cells) are crucial in immune aging. This specific subset of effector memory T cells has terminally differentiated properties and exhibits high cytotoxicity and proinflammatory capacity. We therefore explored and described the interplay between exhaustion features, essential markers, functions, and signaling pathways from previous studies on HIV, antiretroviral therapy, immune senescence, and TEMRA cells. Their remarkable antiviral capacity is then highlighted by elucidating phenotypic changes in TEMRA cells during HIV infection, describing changes in TEMRA cells before, during, and after antiretroviral therapy and other drug treatments. Their critical role in complications and cytomegalovirus (CMV)-HIV superinfection is highlighted. These studies demonstrate that TEMRA cells play a key role in the antiviral response and immune senescence during HIV infection. Finally, we review current therapeutic strategies targeting TEMRA cells that may be clinically beneficial, highlight their potential role in HIV-1 vaccine development, and provide perspectives and predictions for related future applications.